Pertumbuhan dan Hasil Tanaman Bawang Merah 'Varietas Lembah Palu' dengan Pola Tanam Berbeda di antara Tanaman Cabai - Ansar, Muhammad; Bahrudin, Bahrudin; Prastyawan, Dwi (Badan Riset dan Inovasi Daerah Sulawesi Tengah, 2019)
Shallot (Allium ascalonicum L.) is one of the leading vegetable commodities that has been cultivated for a long time by farmers intensively. Along with the increasing population growth, demand for these two commodities continues to increase while production is still very low. With the improvement of the fencing cropping system, production potential can be achieved in order to increase crop production. This study aims to obtain the treatment of cropping patterns. right on the chili fence plants on the growth and yield of shallots. This study used a randomized block design method with 4 treatments consisting of P1 (monoculture/control cropping pattern), P2 (stripping pattern 2: 1), P3 (zigzag cropping pattern), and P4 (mixed cropping pattern). Based on the results of the study, it was found that all treatments of the planting pattern of valley shallot varieties between the chili hedgerows i.e. monoculture, strips of 2: 1, zigzag and mixture showed no significant effect on the growth and yield of shallots. This means that all the shallots cropping patterns that were tried can be applied to planting shallots among the chilies.